Determination of hydrodynamic parameters of the compressive shock wave in the plasma containment process. - Hazim Mahmood; Nabhan Hamdoon; Salah Sheet (College of Education for Pure Sciences, 2009)
Abstract: Determination of hydrodynamic parameters of shock wave were performed in the inertial plasma confinement which includes: Pressure, Speed, Mach number, Density of the two region(up stream and down stream) for the assumed fuel pellet. The shock wave created via the ablation of the outer shell of fuel pellet, through exposed it the laser and consequently caused to compressed the liquid fuel material (D-T) to moved directed to the center of pellet. Coding of numerical solutions (finite difference technique) of hydrodynamic equations by using a scientific language Matlab version (R2006a) in the smoothing and drawing of the data.